Relaxin induces up-regulation of ADAM10 metalloprotease in RXFP1-expressing cells by PI3K/AKT signaling. (5th September 2018) - Boccalini, Giulia; Sassoli, Chiara; Bani, Daniele; Nistri, Silvia
Abstract: ADAM10 metalloprotease is required for activation of Notch-1, a transmembrane receptor regulating cell differentiation, proliferation and apoptosis, whose intracellular proteolytic fragment NICD mediates some key cardiovascular effects of the hormone relaxin (RLX). This study demonstrates the involvement of ADAM10 and PI3K/Akt signaling in mediating RLX-induced Notch-1 activation. H9c2 cardiomyocytes and NIH3T3 fibroblasts were incubated with human RLX-2 (17 nmol/l, 24 h) in presence or absence of the PI3K or Akt inhibitors wortmannin (WT, 100 nmol/l) and triciribine (TCN, 1 μmol/l). Cyclohexanedione-inactivated RLX (iRLX) served as negative control. RLX significantly increased Akt phosphorylation, ADAM10 and NICD expression, which were abolished by WT or TCN and did not occur with iRLX. These findings highlight a new receptor-specific signal transduction pathway of RLX. Graphical abstract: Highlights: A new mechanism of action for relaxin hormone is proposed. Relaxin increases ADAM10 expression in rat myocardial cells and mouse fibroblasts thereby exerting beneficial effects. Relaxin up-regulats ADAM10 by RXFP1/PI3K/Akt signaling. By this pathway, relaxin induces Notch-1 activation.